PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP MOTIVASI SISWA : SYSTEMATIC LITERATURE REVIEW - Putri Qalbina; Nosi Qadariah (BEST Journal (Biology Education, Sains and Technology), 2025)
Abstract: One of the success factors of students in learning is the use of innovative learning models and motivation to learn in students. One learning model that can increase student learning motivation is the Project Based Learning (PjBL) learning model. The purpose of this study was to analyze the influence of the Project Based Learning learning model in increasing student motivation. The research method used is systematic literature review. The data used in this study were obtained from previous research, in the form of articles related to the Project Based Learning learning model and student motivation. The results of the analysis of several articles show that there is an effect of project based learning on student motivation, both in elementary school students and high school students. This increase in motivation is also supported by the enthusiasm of students in working on projects in learning. The project carried out is a fun thing for students. Therefore, it can be concluded that the project based learning learning model has an effect on increasing student motivation